The Exposures of Loneliness in Harry Styles' As It Was - Rommel Utungga Pasopati; Eka Hesty Rohma Darmawati; Katarina Surensa; Yasmine Azzah Adillah Wirnoto (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
This research is a study to reveal loneliness in Harry Styles’ song As It Was. Loneliness is very subjective and is widely considered a stable attribute by psychologists, which means that individuals have distinct set-points for feeling lonely, and they vary around these set-points based on their life circumstances. On this song, Harry Style talks about accepting change, losing and, rediscovering oneself. So, how may loneliness be exposed in Harry Styles' As It Was? Using qualitative method by listening, quoting, and analyzing written resource, this research is reviewed with Robert S. Weiss’ Social Needs Theory of six social demands that, if unfulfilled, contribute to feelings of loneliness. Those are attachment, social integration, nurturance, affirmation of value, a sense of trusted partnership, and guidance in difficult times. In conclusion, the song depicts loneliness, especially due to the lack of social integration with other persons.